The social construction of fisherwomen towards underage marriage in Sulaa Village, Betoambari District, Bau-Bau City, Southeast Sulawesi - Yusran Suhan; Sakaria Anwar; Nuvida Raf; Hasbi Hasbi; Manyus Radjab; Muhammad Sabiq (Sekolah Tinggi Ilmu Pertanian Wuna, 2022)
The practice of underage marriage to fisherwomen is based on the socio-economic and cultural conditions of the community in constructing a social phenomenon. Underage marriage is a classic discourse that has occurred in society, both in urban, rural and coastal communities. Communities that practice underage marriages are usually influenced by the constructs that develop in the surrounding community. This paper uses a type of qualitative research with a purposive sampling approach. The type of research used is descriptive, based on case study research and documents (both printed and electronic), as well as other sources of information deemed relevant. The results of the study show that the practice of underage marriage occurs because of habitus or habits that are produced from the low economic conditions of fishing families so that underage marriage is considered as a solution for survival and also as social capital and cultural capital owned by fishing families, as well as the practice of buying age and the strength of religious knowledge is a supporting factor for the practice of underage marriages occurring in the area.